The Evidence-Based Practice Silent Enemy: Retracted Articles and Their Use in Systematic Reviews - Herrera Peco, Ivan; Santillán García, Azucena; Morán, José María; Goodman Casanova, Jessica Marian; Cuesta Lozano, Daniel (My University, 2021)
Today, evidence-based nursing practice strives to improve health care, ensure adherence to treatment, improve health outcomes, and guarantee patient safety. The main scientific documents that nurses should consult, to obtain the best possible evidence, are systematic reviews and meta-analyses. However, this type of scientific document has a major issue if it uses retracted articles that could directly a ect the consistency of the results shown in the reviews. The aim of this commentary is to present the current issue represented by the use of retracted articles in meta-analyses of systematic reviews and how researchers could detect them, through the use of di erent instruments, avoiding them, and providing a reliable SR or meta-analysis that could be useful for day-to-day clinical and research activities. Keywords: evidence-based practice; research methodology; nurses; retracted articles